(untitled) (Revista de Ciências Agroveterinárias, 2002)
The aim of this study was to evaluate the ultra- rapid freezing of bovine embryos in vivo produced. Eight Bos taurus cows were submitted to embryo collection on day seven after multiple ovulation estrous induction. Only embryos at the late morulae and early blastocyst stage, and classified as grade one or two, according International Embryo Transfer Society (IETS), were used. After selected, twenty-seven embryos were exposed to a solution with 3.0M of glycerol and 0.25M of sucrose in Dulbecco’s medium (DPBSm), and individually loaded in 0.25ml straw. After 10 minutes, the straw was placed on a 1.5cm height styrofoam platform maintained floating in the liquid nitrogen. The straw was maintained in the cold vapor during one minute and then plunged in the liquid nitrogen. The warming was performed by five seconds air exposure, followed by the submersion in a 35C water-bath during 20 seconds. The intracellular cryoprotectant removal was performed by the use of an osmotic 0.25M sucrose gradient, during 10 minutes, followed by DPBSm to complete the rehidration. The embryos were then loaded in 0.25ml straws and inovulated in synchronous recipients, by transcervical method. Twenty-six of twenty-seven frozen embryos were transferred, resulting in five pregnant (19.2%) recipients, and born of five healthy and normal calves. We conclude that the ultra-rapid freezing method permits the cryopreservation of in vivo bovine embryos, however the pregnancy rates are still lower than that obtained with the conventional freezing method, indicating the need of new investigations to adequate the method for bovine embryos.